4PBA strongly attenuates endoplasmic reticulum stress, fibrosis, and mitochondrial apoptosis markers in cyclosporine treated human gingival fibroblasts. Issue 1 (27th April 2017) - Ranga Rao, Suresh; Subbarayan, Rajasekaran; Ajitkumar, Supraja; Murugan Girija, Dinesh
Abstract : Cyclosporine induces overgrowth of human gingiva. Previously we have shown (i) cyclosporine—inducing ER stress in human gingival fibroblasts (HGF), (ii) increased matrix protein expression, and (iii) interference with mitochondrial pro‐ and anti—apoptotic factors. This study was undertaken to assess the effects of melatonin (an antioxidant), 4PBA (an ER stress inhibitor), and simvastatin on the expression of ER Stress markers as well as on matrix and mitochondrial markers. HGF incubated with cyclosporine, or without melatonin/4PBA/statin. After 24 hr of incubation, mRNA expression of ER stress markers (GRP78, CHOP, XBP1, and XBPs) and matrix protein markers (like α‐SMA, VEGF, TGF‐β, CTGF), and mitochondrial apoptosis markers estimated and compared with housekeeping gene GAPDH. Compared to the control cyclosporine significantly augmented ER Stress and matrix proteins, which decreased significantly with the use of melatonin, 4PBA, and simvastatin. The mitochondrial proapoptotic molecule cyclophilin D, as well as Bcl2 expression also decreased after PBA treatment, paralleling an increase in cytochrome c expression. The effect of 4PBA was much more pronounced than the influence of other two. In conclusion, 4PBA could be a viable therapeutic option for drug‐induced gingival overgrowth. Abstract : The effect of 4PBA was much more pronounced than the influence of other two. In conclusion, 4PBA could be a viable therapeutic option for drug‐induced gingival overgrowth.